Profil Kemampuan Motorik Dasar Anak Usia 11 Tahun Berdasarkan Instrumen MoBAK di Pangalengan - Hadi Harta Piana; Iman Imanudin; Syam Hardwis (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to analyze the profile of basic motor competence among 11-year-old children in the Pangalengan area using the MoBaK instrument. The study employed a quantitative descriptive method with a survey approach. The sample consisted of 141 children aged 11 years from several elementary schools in Pangalengan selected using total sampling techniques. The research instrument used the MoBaK test, which consists of two main domains: self movement and object movement. Data were analyzed descriptively using mean, percentage, standard deviation, minimum, and maximum scores. The results showed that children’s self movement abilities tended to be in the moderate category, while object movement abilities were generally in the good category. These findings indicate that children’s object control skills developed better than their self movement abilities. The differences between the two domains were influenced by physical activity experiences, movement environments, and children’s involvement in play activities. This study provides empirical information regarding the condition of basic motor competence in elementary school children and may serve as a basis for developing more targeted physical education and physical activity programs Keywords: Elementary School Children, Motor Competence, MoBak, Object Movement, Self Movement